Self-assembly and activation of a titania-nanotube based photocatalyst for H-2 evolution - Fu, Fan; Wu, Zhenni; Cha, Gi; Schmuki, Patrik (Chemical Communications, 2021)
Constructing an efficient photocatalyst for H-2 production generally requires the integration of several functional features in and on a semiconductor platform. This is conventionally done by a classic step-by-step synthesis. Here, we report the self-assembly of an amorphous titania nanotube based system when illuminated for extended time in suitable aqueous solutions. Over time, not only photodeposition of a co-catalyst can take place, but also in situ crystallization and morphology changes occur that can provide a higher H-2 production than observed for a classically assembled photocatalyst.
CRIS-Team WoS Importer:2021-07-09